High-performance work systems, innovation and knowledge sharing: An empirical analysis in the context of project-based organizations - Bhatti, Sabeen Hussain; Zakariya, Ramsha; Vrontis, Demetris; Santoro, Gabriele; Christofi, Michael (My University, 2021)
Purpose: This article aims to explore the relationship among high performance work systems (HPWS), innovation, and knowledge sharing in project-based organizations. Design/methodology/approach: Using the ability, motivation, and opportunity (AMO) framework under the theory of HPWS, our article hypothesizes that the AMO enhancing practices of project-based organizations lead to better innovation performance of their employees through the mediating role of knowledge sharing. Time-lagged data of AMO practices and knowledge sharing practices were collected from the employees of these organizations over three weeks. Furthermore, the innovation performance data were collected from the supervisors of these employees over an additional three-week period. Findings: Our results confirm the initial hypothesis of the causal relationship of two of the AMO HRM practices, that is, ability and motivation with innovation performance with the mediation of knowledge sharing, while the third hypothesis of opportunity enhancing HRM practice was not accepted. Originality/value: This research has implications for both theory and practice and it can help the project managers of these organizations to better design HRM practices in order to improve the creativity and innovation performance of their employees. Accordingly, this is one of the first studies dealing with the effectiveness of HRM on AMO, and the key role of knowledge sharing.
Keywords: Ability motivation opportunity framework; High performance work systems; Innovation; Knowledge sharing